1994
DOI: 10.1080/00288233.1994.9513040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Friesian, Friesian‐Jersey‐cross, and Jersey steers in beef production

Abstract: An account is given of the rearing in one unit of 274 Friesian, Jersey, and FriesianJersey-cross male calves and of their subsequent growth to approximately 22-23 months of age. A sample of the 10 heaviest of each breed group was selected for slaughter at 22-23 months of age. The Friesian steers in this sample were 6.8% heavier than the Jersey steers. Their heavier carcass weight and higher grades gave them a monetary advantage of $NZ9.42 over the average Friesian-Jersey-cross carcass and an advantage of $NZ32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 2 publications
4
16
2
Order By: Relevance
“…Both studies agree that carcass conformation class was significantly better for the Norwegian Red animals while carcass fat class did not differ. The lower carcass weight, kill out proportion, carcass conformation class and carcass fat class for JE would be expected from the lower slaughter weight and are in general agreement with the findings of Barton et al (1994) and Alberti et al (2008) for a comparison of Holstein and Jersey pure-bred bulls. The 15 g/kg difference in kill out proportion in favour of the bulls over the steers compares with values of 23 g/kg (Keane, 2003) and 13 g/kg (McGee et al, 2005;Campion et al, 2009a).…”
Section: Carcass Traitssupporting
confidence: 78%
“…Both studies agree that carcass conformation class was significantly better for the Norwegian Red animals while carcass fat class did not differ. The lower carcass weight, kill out proportion, carcass conformation class and carcass fat class for JE would be expected from the lower slaughter weight and are in general agreement with the findings of Barton et al (1994) and Alberti et al (2008) for a comparison of Holstein and Jersey pure-bred bulls. The 15 g/kg difference in kill out proportion in favour of the bulls over the steers compares with values of 23 g/kg (Keane, 2003) and 13 g/kg (McGee et al, 2005;Campion et al, 2009a).…”
Section: Carcass Traitssupporting
confidence: 78%
“…In the present study, there were no differences [P > 0.05) reported for dressing percentage, KPH, and USDA Yield grade between the Jersey treatment groups. Although KPH was not different in the present study, others have reported that internal (KPH) fat is greater for Jersey steers and bulls compared with Holstein steers and bulls (Talamantes et al, 1986;Barton et al, 1994Barton et al, , 1997, and at similar amounts of subcutaneous fat, Jersey carcasses had greater KPH and intramuscular fat than Holsteins (Butler-Hogg and Wood, 1982). Because Jerseys deposit fat in various depot sites differently than Holsteins, Jerseys have greater trim loss (Lehmkuhler and Ramos, 2008).…”
Section: Resultscontrasting
confidence: 45%
“…Jersey cattle demonstrate the potential to produce a highly marbled product (Alberti et al, 2008) and thus may create the opportunity for a niche market. However, Jerseys are recognized as one of the slowest growing breeds of cattle (Barton et al, 1994;Alberti et al, 2008;Lehmkuhler and Ramos, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Naude & Armstrong [9] also found low growth rates and efficiency of gain for purebred Jersey steers in comparison to beef-Jersey crossbred steers, and the weight gain of Jersey bulls was improved by 39% from crossbreeding with Simmental bulls. Jersey steers grew slowly and when slaughtered at 22 -23 months of age, their carcass were too light [10]. Reported heavier carcass weight for beef crosses in this study were consistent with the study by [11] who found carcass weight of Jersey to be lower than that of crossbreds on beef production of Belgian-Blue/Jersey, Limousin/Jersey and Jersey cattle in a pasture-based system.…”
Section: Discussionsupporting
confidence: 82%
“…32 and 31 vs. 24 kg, respectively [11]. Purchas et al, [16] and [10] also found that the disadvantages of purebred Jersey cattle in beef production were greatly reduced by crossbreeding with beef breeds. Breed cross effect became more evident and the live weight advantage continued through to slaughter with crosses being significantly heavier at birth, weaning and at the final weighing prior to slaughter [17].…”
Section: Discussionmentioning
confidence: 99%